2017
DOI: 10.1172/jci.insight.92970
|View full text |Cite
|
Sign up to set email alerts
|

Integration of homeostatic signaling and food reward processing in the human brain

Abstract: IntroductionThe consumption of food is necessary for our everyday survival and is promoted by an intricate network of complex homeostatic and hedonic interactions. Hunger is a motivational state considered as an endpoint of these elements; it ensures that we actively seek out food when necessary. However, hunger is not only the result of simple energy deficiency; it has emerged as a product of a complex biopsychological and environmental interaction. Given the rapid development of obesity worldwide, a better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 88 publications
1
44
1
Order By: Relevance
“…In humans, changes in brain activity can be detected by different methods, such as functional magnetic resonance imaging and positron emission tomography . The central nervous system plays a key role in homeostasis, control of food intake and perception of conscious sensations …”
Section: Physiological Response To Eatingmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, changes in brain activity can be detected by different methods, such as functional magnetic resonance imaging and positron emission tomography . The central nervous system plays a key role in homeostasis, control of food intake and perception of conscious sensations …”
Section: Physiological Response To Eatingmentioning
confidence: 99%
“…Indeed, homeostatic and hedonic sensations are dissociable, so that postprandial satiety/fullness may have a satisfactory or an aversive dimension depending on several conditions, including the type of meal, the digestive response and other conditioning factors (see below). Some data indicate that homeostatic and hedonic sensations are mediated by different mechanisms . Indeed, recent studies have shown that homeostatic and hedonic sensations are selectively related to specific changes in circulating metabolites as well as in brain activity …”
Section: The Postprandial Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Nodes were defined from Power's atlas with 264 brain regions . We used the reward‐related nodes reported by previous studies as seed nodes . The selected reward‐related nodes are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…When we receive a food cue, multiple neural processes are triggered in the brain; these processes are involved in food preference, the timing of food intake, and eating patterns. Furthermore, hunger is a motivational state that can drive us to find food, but hunger is more than a mere drive to supplement the body's energy supply; hedonic feelings are generated by an intricate neural network when we consume food . The neural processing of food can be divided into perceive hedonic feeling and incentive motivation generated by energy needs of the body .…”
mentioning
confidence: 99%